A escola de ensino fundamental vivida pelo aluno, revelada por seus diários - Sena, Clério Cezar Batista (2010)
The current study aimed the investigation upon what the diaries of students from the fourth grade of primary school in a public school in a city near São Paulo could reveal. Based on Henri Wallon‟s theory about affection and environment, this research has as documents the diaries written in 2005 with didactic purposes, at the time. Later on, these diaries became the object of the current study. The data analysis was developed through themes, searching for the revelations within the diaries, as well as: 1st confidant, close friend; 2nd depository of emotions and feelings: a) happiness; b) sadness; c) anger; d) fear; 3rd communication tool between the teachers and his students; 4th a tool for students‟ sociocultural environment knowledge. The results indicate that the diary allowed the affective relations between teacher and students to be tightened, a better knowledge form the teacher‟s point of view on the students‟ socio-cultural reality and also an affective relation form the students in relation to the diaries. This diary came to be for some of the students the meaningful other, a friend to whom they could reveal a secret and unburden their hearts, manifesting themselves entirely. Therefore, the diaries as methodological or pedagogical instruments allow a better knowledge from the students about themselves as a person: affection, knowledge and movement